Tingkat Kerentanan Penghidupan Nelayan Pantai Kedonganan dalam Menghadapi Variasi Musim di Kabupaten Badung (Jurnal Agribisnis dan Agrowisata, 2026)
The Level of Livelihood Vulnerability of Kedonganan Coast Fishermen in Facing Seasonal Variations in Badung District. Seasonal changes result in shifts in fishermen's fishing patterns and make water conditions difficult to predict. The phenomenon of the west and east seasons is a barrier for fishermen on Kedonganan Beach in looking for marine products. As a result of seasonal changes, fishermen must be alert to changes in nature and weather. The aim of this research is to analyze the income of fishermen in the normal, east and west seasons and estimate the value of fishermen's vulnerability in facing seasonal variability on Kedonganan Beach, Kuta District, Badung Regency. The research method used in this research is the multiple linear regression analysis method using the classic assumption test using SPSS version 25 and calculating the vulnerability index using the Livelihood Vulnerability Index (LVI) calculation. The results of this research show that Based on the results of the previous discussion, it can be concluded that the average annual income of fishermen is IDR 52,758,999, with the lowest to highest income occurring in the west season (IDR 14,886,413), east season (IDR 18,149,694), and summer season (IDR 19,722,892). Fishermen's income is higher in the normal and eastern seasons than in the western season, even though the selling price of fish in the eastern season is cheaper than in other seasons. Regression analysis shows that factors such as the number of days at sea, distance traveled, working hours at sea, and experience as a fisherman influence the income of fishermen on Kedonganan Beach, with an independent variable contribution of 72.9%. The LVI values for the Putra Bali (0.387), Ulam Sari (0.371), Wana Segara Kertih (0.363), Segara Ayu (0.366) and Kerta Bali (0.384) fishermen groups indicate that the fishermen groups on Kedonganan Beach are in the category of being vulnerable to seasonal variability.
Keywords: livelihood vulnerability index; fishermen's income; vulnerability level; seasonal variability